Sodium–glucose cotransporter 2 inhibitors improved time‐in‐range without increasing hypoglycemia in Japanese patients with type 1 diabetes: A retrospective, single‐center, pilot study. Issue 5 (27th March 2020) - Suzuki, Daisuke; Yamada, Hodaka; Yoshida, Masashi; Funazaki, Shunsuke; Amamoto, Misato; Morimoto, Jun; Hara, Kazuo
Abstract: Aims/Introduction: Studies have shown that sodium–glucose cotransporter 2 (SGLT2) inhibitors increased time‐in‐range (TIR; percentage of time glucose level remains between 3.9 and 10.0 mmol/L [70–180 mg/dL]) and decreased glycemic variability in patients with type 1 diabetes. The aim of this study was to investigate the effects of SGLT2 inhibitors on TIR, glycemic variability and glucose control in Japanese patients with type 1 diabetes in a real clinical setting. Materials and Methods: We designed a single‐arm, retrospective cohort study to analyze data from patients starting to use ipragliflozin or dapagliflozin and who used a sensor‐based flash glucose monitoring system between February 2019 and August 2019. We measured TIR, time above range >180 mg/dL (percentage of time with glucose level of >180 mg/dL or >10.0 mmol/L), time below range <70 mg/dL (percentage of time with glucose level of <70 mg/dL or <3.9 mmol/L), mean glucose and standard deviation, and coefficient of variation for glycemic variability, and then compared the data before and after SGLT2 inhibitors treatments. Results: We enrolled 15 patients in the study. The total dosages of basal insulin decreased significantly, but the total doses of bolus insulin did not change significantly. TIR increased significantly by approximately 11.6%; the time below range <70 mg/dL remained unchanged; and the mean glucose and standard deviation decreased significantly, whereas the coefficients of variation did not. Conclusions: SGLT2 inhibitors improved TIR and the mean glucose level and standard deviation without increasing the time below range <70 mg/dL in patients with type 1 diabetes. Abstract : Our results have implications for recommendations regarding treatment of patients with type 1 diabetes, as they suggest that sodium–glucose cotransporter 2 inhibitors might help them improve their glycemic control.